2017
DOI: 10.1002/ijc.31209
|View full text |Cite
|
Sign up to set email alerts
|

p53 and miR‐210 regulated NeuroD2, a neuronal basic helix–loop–helix transcription factor, is downregulated in glioblastoma patients and functions as a tumor suppressor under hypoxic microenvironment

Abstract: The factors involved in cell differentiation have recently garnered interest for their role in inhibition of pathogenesis in various tumors. However, their role in glioblastoma (GBM) remains poorly understood. We analyzed The Cancer Genome Atlas (TCGA) GBM data and found significant downregulation of neurogenic differentiation factor NeuroD2 in GBM patients. Low levels of NeuroD2 were found to be correlated with poor overall survival of GBM patients in TCGA dataset as well as in our cohort. Interestingly, Neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…We found that expressions of a set of neurogenic transcription factors, such as Neurod2, Ascl1 and Myt1l, were increased during GBM-neuron cell conversion. Neurod2 is significantly downregulated in GBM patients, which is involved in the p53 pathway [ 63 ]. Ascl1 and Myt1l suppress GBM tumorigenicity and are required for glioblastoma stem cells to undergo neuronal lineage differentiation [ 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that expressions of a set of neurogenic transcription factors, such as Neurod2, Ascl1 and Myt1l, were increased during GBM-neuron cell conversion. Neurod2 is significantly downregulated in GBM patients, which is involved in the p53 pathway [ 63 ]. Ascl1 and Myt1l suppress GBM tumorigenicity and are required for glioblastoma stem cells to undergo neuronal lineage differentiation [ 64 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that miR‐145 inhibits non‐small‐cell lung cancer growth by targeting RIOK2 31 . NeuroD2 is post‐transcriptionally targeted by miR‐210, overexpression of NeuroD2 diminishes glioma cell proliferation, migration, and promotes apoptosis under hypoxia 18 . MiR‐4744 was originally identified by second‐generation sequencing in breast cancer tissues 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive studies have revealed the dysregulation of miRNAs in the progression of gliomas. For example, miR‐210 strictly regulates the expression of NeuroD2, and overexpression of NeuroD2 reduces the invasiveness of glioblastoma under hypoxia conditions 18 . The level of miRNAs in cerebrospinal fluid and brain tissue of glioma patients is a reliable marker and may have diagnostic value for glioma 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, inhibition of this pathway could be a potential strategy to enhance sustained TMZ-response in this malignancy. Agrawal et al identified a novel role of NeuroD2 as a tumor suppressor and prognostic biomarker in GBM the levels of which are tightly regulated by p53 and miR-210 [20]. Overexpressing NeuroD2 may potentially be a simple and efficient therapeutic strategy to inhibit the malignant phenotype of GBM cells [20].…”
Section: Discussionmentioning
confidence: 99%